Engineering computations an introduction using MATLAB and Excel - Musto, Joseph C. (McGraw-Hill's BEST--basic engineering series and tools, 2009)
Focuses on the fundamentals of engineering computing: algorithm development, selection of appropriate tools, documentation of solutions, and verification and interpretation of results.